Cultural Resistance, Output Measures, and Audit Practice: Impact on Non-Implementation of Program-Based Budgeting in Nigeria. Issue 12 (14th October 2016) - Avwokeni, Arthur J.
ABSTRACT: Excessive spending on recurrent expenditure hampers economic growth. A program-based budgeting approach has been proposed to discipline fiscal excesses of agencies outside direct civil service machinery but government is inactive. This study hypothesized that difficulty in securing output measures, resistance from politicians, agency heads, and workers; current audit practice; and cost–benefit considerations, hinder implementation. Analysis of perceptual data reveals that resistance from politicians and employees is the major factor that hinders implementation of a program-based budgeting in Nigeria. In addition, difficulty in securing measures to quantify outputs thwarts implementation initiatives, and current audit practice whereby private audit firms audit operational activities of agencies only at year-end subvert program reviews. The study recommends that politicians be advised on political considerations in budgetary allocation; a performance measurement committee be set up to develop measures of outputs acceptable to workers; and a body of auditors be nationalized to undertake audit of government agencies.